Life-history trade-offs, density, lay date—not personality—explain multibroodedness in great tits. (21st July 2021) - Senécal, Sarah; Mouchet, Alexia; Dingemanse, Niels J
Abstract: In various taxa, multibroodedness is a common breeding strategy. Life-history theory predicts that individuals can increase fitness by producing multiple broods within a season. Despite the apparent increase in the number of offspring parents might produce per season, not all individuals are multibrooded, suggesting a trade-off. We studied ecological and behavioral factors influencing the initiation of second clutches in great tits ( Parus major ), an optionally multibrooded bird species, by distinguishing two types of clutches: replacement versus true second clutches, produced after failure versus successful first breeding attempts, respectively. We predicted which lay date, density, and investment in first clutches would decrease the probability of initiating a second clutch, but which faster exploring behavioral types with a faster pace-of-life would be more likely to be multibrooded. The probability of initiating true second clutches varied negatively within-individuals with lay date and breeding density. The initiation of replacement clutches instead varied negatively among-individuals with lay date and density, suggesting nonrandom settlement of behavioral types across environments. Individuals were less likely to be multibrooded when producing many offspring from their first clutch, suggesting within-year reproductive trade-offs, similar to previous studies. No previous research has linked personality to multibroodedness; here we show which neither the repeatable nor the plastic part of an individual's exploratory behavior predicted multibroodedness. We confirmed our prediction which the resolution of trade-offs may occur either at the within- or among-individual level. Our research contributes to the understanding of life-history evolution in the wild by studying the mechanisms shaping multibroodedness within seasons. Abstract : In many birds, multibroodedness represents an optional reproductive strategy. We show for a nest box breeding passerine that the decision to produce multiple broods per season depends on the bird's initial lay date, breeding density, and the success of their first brood. Birds were more likely to produce a second brood when they were breeding early and under low densities, but these effects differed according to their first brood's success. Multibroodedness was not part of a personality-related life-history strategy.